2021
DOI: 10.1142/s0219720021500311
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cancer-related module in protein–protein interaction network based on gene prioritization

Abstract: With the rapid development of deep sequencing technologies, a large amount of high-throughput data has been available for studying the carcinogenic mechanism at the molecular level. It has been widely accepted that the development and progression of cancer are regulated by modules/pathways rather than individual genes. The investigation of identifying cancer-related active modules has received an extensive attention. In this paper, we put forward an identification method ModFinder by integrating both biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The disease modules, which consist of a known group of genes found in cancers like breast, sarcoma, colorectal, leukemia, and head and neck cancer, were linked to biological processes that are unique to cancer [ 12 ]. Wu et al [ 13 ] showed that the active disease modules in breast and cervical cancer are associated with many cancer-related pathways. These studies indicate that the identification of cancer-specific disease modules can help identify novel biomarkers for therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…The disease modules, which consist of a known group of genes found in cancers like breast, sarcoma, colorectal, leukemia, and head and neck cancer, were linked to biological processes that are unique to cancer [ 12 ]. Wu et al [ 13 ] showed that the active disease modules in breast and cervical cancer are associated with many cancer-related pathways. These studies indicate that the identification of cancer-specific disease modules can help identify novel biomarkers for therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%